PARTISIPASI PROGRAM MBG DAN STATUS GIZI TERHADAP KONSENTRASI BELAJAR PADA SISWA SMA KEMALA BHAYANGKARI 1 JAKARTA - Intan Asri Nurani; Nur Fajariyah; Yuliana Pungki (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Nutritional status plays a crucial role in supporting learning concentration among adolescents aged 15–18 years, as evidenced by the 2023 Indonesian Health Survey (SKI) showing 7–8% underweight, 12.1% overweight, and 4.1% obese cases, reflecting a double burden of malnutrition that may disrupt learning processes; therefore, the MBG (Free Nutritious Meal) program is designed to improve students' nutritional status to enhance concentration and human resource quality. This study examined the relationship between MBG program participation and nutritional status on learning concentration in 94 students at SMA Kemala Bhayangkari 1 Jakarta using a cross-sectional design with stratified sampling, where the Chi-Square test indicated a significant association for MBG participation (p=0.026) and Fisher's Exact test for nutritional status (p=0.001). The main conclusion is a significant relationship between both factors and learning concentration, with recommendations for future research to employ more comprehensive instruments for accurate MBG participation measurement to ensure result objectivity.